Understanding of the occurrence of intergranular corrosion in 2024 aluminum alloy under atmospheric environment - Baoyu Cai; Zhenchang Xu; Guipeng Liu; Yuan Li; Luchun Yan; Xiaolu Pang; Kewei Gao (Journal of Materials Research and Technology)
The evolution process of 2024-T351 aluminum alloy from pitting corrosion to intergranular corrosion has been studied using atmospheric environment exposure and quasi-in-situ droplet corrosion methods. The multiple corrosion pits (planet-type pits) covered within the corrosion ring are the corrosion areas that require special attention. The large number of Cu-rich remnants left by the pit accelerates intergranular corrosion of the grain boundaries on the surface. This allows surface intergranular corrosion to occur before the pit encounters the grain boundary downward. This study therefore provides an additional understanding of the conventional intergranular corrosion process.